Condições de acessibilidade dos centros acadêmicos universitários: criação de um instrumento de avaliação - Nascimento , Flaviano Batista do (2017)
With the aim of subsidizing students with disabilities and reduced mobility in achieving equality, equity of opportunity and space in academic society in their total or partial university experience, presented himself, as objective of our research, the creation of an evaluation instrument that has as result an indicator of the level of accessibility of the university academic centers of Higher Education Institutions (IES), having as a case study the Center of Legal Sciences (CCJ) of the Federal University of Paraíba (UFPB). The developed instrument measured the accessibility of the academic structure that configures university academic centers based on technical and instrumental parameters that make up the dimensions: architectural, communicational; methodological; instrumental; programmatic and attitudinal. As a result, a global indicator was presented – Indicator A6 – which testifies to how accessible the academic university center under study, contributing to the management, mobilization, debate and evaluation of the institutional actors, in view of the importance of promoting accessibility as an empowerment for admission, permanence and completion of higher education of those historically marginalized.